Pemutihan kembali gigi yang berubah warna pada anak Dental bleaching on children with discolored teeth - Roedy Budirahardjo (DiscoverSys Inc., 2011)
Dental bleaching is a process making teeth look whiter. Bleaching may be performed in two methods; by usingbleaching products or non-bleaching products. Bleaching products contain peroxide assisting to remove intrinsicand extrinsic stain, resulting in the changing of original color of teeth. Non-bleaching products contain materialsthat may work to remove extrinsic stain only, through both physical and chemical actions. The use of bleachingproducts is not always safe, therefore, they should be assumed that their benefits are over their recognizedbiological risk. The choice of bleaching method for children depends on type and depth of the stain, and discoloring.Stain on the enamel surface can be removed by microabration, deeper stain is removed by bleaching. Besides usingapproved by ADA/ISO, a dental practitioner should have knowledge about dental bleaching and its use at clinic andat home, including its contraindication as well as side effect in order to provide an effective and satisfying dentalbleaching care.